2017
DOI: 10.1080/03050068.2017.1334428
|View full text |Cite
|
Sign up to set email alerts
|

Truth commissions, education, and positive peace: an analysis of truth commission final reports (1980–2015)

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/userguides/explore-bristol-research/ebr-terms/ Truth commissions, education and positive peace: an analysis of truth commission final reports (1980 -2015)Abstract Transitional justice and education both occupy increasingly prominent space on the international peacebuilding agenda, though less is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Similarly, academics can help communities to explore the underlying drivers of conflict and suggest new ways forward that avoid reproducing the social conditions that led to conflict. University staff and students might also mobilise for forms of transitional justice (Paulson and Bellino, 2017) or create and propagate constructive discourses, and practices, of commemoration (Pacheco, 2013). Furthermore, campuses themselves are sites where people from across wartime social fracture lines can meet and engage in dialogue (Davies, 2004).…”
Section: Critical Voice and Universities As Social Groupsmentioning
confidence: 99%
“…Similarly, academics can help communities to explore the underlying drivers of conflict and suggest new ways forward that avoid reproducing the social conditions that led to conflict. University staff and students might also mobilise for forms of transitional justice (Paulson and Bellino, 2017) or create and propagate constructive discourses, and practices, of commemoration (Pacheco, 2013). Furthermore, campuses themselves are sites where people from across wartime social fracture lines can meet and engage in dialogue (Davies, 2004).…”
Section: Critical Voice and Universities As Social Groupsmentioning
confidence: 99%
“…It is therefore not surprising that the most frequent educational engagement of truth commissions is to recommend educational content. An analysis of truth commission final reports (Paulson and Bellino, 2017), for example, found that 16 reports called for non-formal education programmes, and 15 reports recommended the development of new content or subject areas within formal education. Furthermore, truth commission reports have provided source material for official textbooks (Bentrovato and Wassermann, 2018) and alternative educational materials developed by human rights organisations in Guatemala (Oglesby, 2007), South Africa (Weldon, 2010) and Peru (Paulson, 2017).…”
Section: Problematising Truth Tellingmentioning
confidence: 99%
“…This was the theme of the wellattended 20 th Anniversary Symposium held in Bristol during May 2018, where the Keynote speaker Arjen Wals, Professor of Transformative Learning for Socio-Ecological Sustainability at Wageningen University in The Netherlands, argued how being 'disruptive' can play a positive role in challenging preconceptions, understanding conflict, and promoting sustainable peace (see https://cireblog.wordpress.com/blog/; Wals, Yoko and Leicht, 2017). Similarly, innovative and challenging work on violent extremism, education and sustainable peace building by Novelli and colleagues (2017;Novelli 2017), studies of inclusivity and transnational justice processes (Paulson and Bellino, 2017), and research priorities stemming from the impact of climate change and sea level rise all have urgent social justice, human rights and global security implications. Such work is vital in our times of economic, cultural and environmental uncertainty, and it highlights the importance of BAICE supporting comparative and educational research on these and related issues across and beyond traditional disciplinary boundaries.…”
Section: Conclusion : Some Implications and Challenges For Baicementioning
confidence: 99%